Pengaruh Corporate Image, Trust, Kepuasan terhadap Loyalitas Konsumen Pusat Oleh-Oleh Khas Kerinci - Gampo Haryono; Albetris Albetris (Universitas Batanghari, 2023)
The Covid-19 pandemic has become a difficult time for several aspects, including the world of marketing. This is also felt by MSME business actors. The use of online media can help the defense and life journey of MSMEs. Loyalty is a strong commitment to encourage customers to visit again (Oliver, 1999). Consumer loyalty (Rauyruen & Miller, 2007; Selnes, 1998) is a manifestation and continuation of customer satisfaction in using the facilities and services provided by the company, as well as to remain a customer of a company. In this study, loyalty was measured using the variables Corporate Image, Trust, Consumer Satisfaction Central By - By Khas Kerinci was chosen as the object of research because of the decline in sales during the Covid-19 pandemic. The study was conducted on 100 consumers of the Center by Khas Kerinci with purposive sampling method, and analyzed using the SPSS 22 program.